Nursing care in organ donation after brain death (Research, Society and Development, 2025)
The present study aimed to analyze nursing care in organ donation to patients diagnosed with brain death, documentary research was carried out using direct sources (legislation and COFEN) and indirect sources through a narrative bibliographic review. Brain death (BD) is the total and irreversible suspension of all brain and brain stem functionality, caused by a serious injury that blocks the blood that reaches the brain region, leading to brain death. The main causes of brain death are traumatic brain injury (TBI), cerebrovascular accident (CVA) and hypoxic-ischemic brain injury.  Organ and tissue donation consists of complex procedures and steps, involving bureaucratic, legal and personal issues for the family members involved and the patient himself, and this process leads to great hope for a cure and restoration of the health of an individual who has been waiting for many years for a transplant due to their serious illness.  COFEN resolutions No. 611/2019 and No. 710/2022 define and update the technical guidelines on the role of the nursing team in the processes of donation, harvesting and transplantation of organs, tissues and cells, ensuring patient safety, that is, among nursing responsibilities, participation in all stages of the donation stands out, in accordance with their technical and legal competencies, in addition to maintaining the hemodynamic stability of the donor, in order to preserve the viability of the organs for transplantation, requiring of professionals the technical-scientific preparation, competence and skill in therapeutic communication and attitudes based on ethics and legality of the processes.